2022
DOI: 10.1172/jci151239
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of neoadjuvant vaccination with tumor-cell lysate induces T cell response in low-grade gliomas

Abstract: BACKGROUND.Long-term prognosis of WHO grade II low-grade glioma (LGG) is poor secondary to risk of recurrence and malignant transformation into high-grade glioma. Given the relatively intact immune system of patients with LGG and the slow tumor growth rate, vaccines are an attractive treatment strategy. METHODS.We conducted a pilot study to evaluate the safety and immunological effects of vaccination with GBM6-AD, lysate of an allogeneic glioblastoma stem cell line, with poly-ICLC in patients with LGG.Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 45 publications
(66 reference statements)
0
22
0
Order By: Relevance
“…Two phase III trials evaluating distinct vaccine approaches for newly diagnosed glioblastoma have been reported. The ACT IV study randomized newly diagnosed glioblastoma patients with EGFRvIII-positive tumors to the standard of care with a placebo or a peptide vaccine to EGFRvIII (NCT01480479) [43 ▪▪ ]. Although nonrandomized studies demonstrated a survival benefit with this vaccine relative to historical controls [41], no improvement in OS was noted in this study.…”
Section: Antitumor Vaccinationmentioning
confidence: 76%
See 2 more Smart Citations
“…Two phase III trials evaluating distinct vaccine approaches for newly diagnosed glioblastoma have been reported. The ACT IV study randomized newly diagnosed glioblastoma patients with EGFRvIII-positive tumors to the standard of care with a placebo or a peptide vaccine to EGFRvIII (NCT01480479) [43 ▪▪ ]. Although nonrandomized studies demonstrated a survival benefit with this vaccine relative to historical controls [41], no improvement in OS was noted in this study.…”
Section: Antitumor Vaccinationmentioning
confidence: 76%
“…OS for this study has not been reported and will require extended follow-up due to the long median OS of patients with low-grade glioma. PFS was 11 months, and there was no difference in PFS between the two arms of the study [43 ▪▪ ].…”
Section: Antitumor Vaccinationmentioning
confidence: 85%
See 1 more Smart Citation
“…The immune activity and stromal activity were remarkably elevated in the high-risk group, which once again reiterated the heterogeneity of the glioma TIME between the two groups. Determining the roles of the signature genes in TIME cell infiltration heterogeneity will be beneficial to better understand the mechanisms of the TIME antitumor immune response and developing novel immunotherapy strategies ( Kim et al, 2022 ; Ogino et al, 2022 ; Tian et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent trials with shared-non-mutated, shared-mutated, and personalized-mutated antigens in peptide + adjuvant forms have been tested, showing safety, an antigen-specific antibody response [ 22 ], sustained memory CD8 + or TH1 CD4 + T cell response against personalized antigen peptides [ 23 ] as well as an association between the development of vaccine-specific CD8 + effector memory cells and median OS [ 24 ]. More recently, a pilot randomized study with pre-surgical vaccinations with GBM stem cell lysate in patients with WHO grade II low-grade glioma demonstrated homing of vaccine-reactive CD8 + T-cell clones and increased tissue resident-like CD8 + T-cells in the surgically resected glioma following the neoadjuvant vaccination [ 25 ].…”
Section: What Is the State Of Io For Brain Tumors In Academia And Non...mentioning
confidence: 99%